Evaluation of alignment of the reimbursement medicines list for children in Albania with the WHO essential medicines list for children - E. Petro; V. Perumal-Pillay; A. K. Mantel-Teeuwisse; H. A. van den Ham; F. Suleman (Taylor & Francis Group, 2024)
Background: The WHO Essential Medicine List for Children was released on the 30th anniversary of the general Essential Medicine List in 2007, to recognise special needs for medicines in children, and to promote the inclusion of paediatric medicines in national procurement programmes. This study aimed to investigate the alignment of the medicines included in the Albanian reimbursement medicines list of the Mandatory Healthcare Insurance Fund (AMHIF) and the Essential Medicine List for Children. Methods: A quantitative evaluation was performed to compare the paediatric medicines included in the 2022 list of the AMHIF and the 2021 WHO Essential Medicine List for Children. In addition, vaccines in the Albanian vaccination programmes for children were compared to the ones listed on the WHO Essential Medicine List for Children. Results: Both lists had a total of 284 active ingredients in common, whereas 14 of 24 vaccines were found to be in common in the Essential Medicine List for Children list and the Albanian vaccination programmes. Conclusions: This is the first study in Albania to investigate the alignment of the WHO EMLc and AMHIF list. In case of the same active ingredient there were many deviations in terms of dosage form, strength and indication.